Association of Blue Light-Filtering Intraocular Lenses with All-Cause and Traffic Accident-Related Injuries among Patients Undergoing Bilateral Cataract Surgery in Finland - Kanclerz, Piotr; Hecht, Idan; Cunha, Mariana [UNESP]; Knyazer, Boris; Laine, Ilkka; Tuuminen, Raimo (American Medical Association (AMA), 2022)
Importance: Blue light-filtering (BLF) intraocular lenses (IOLs) have been widely used in clinical practice for more than 20 years and have been implanted in millions of patients with cataracts worldwide. However, little evidence on the association of BLF IOLs with injuries is available. Objective: To assess the association of BLF IOLs with all-cause and traffic accident-related injuries and quality of vision while driving after bilateral cataract surgery. Design, Setting, and Participants: This retrospective registry-based cohort study included patients who underwent bilateral cataract surgery between September 3, 2007, and December 14, 2018, and were followed until December 14, 2021. Surgery was performed at the Department of Ophthalmology, Kymenlaakso Central Hospital, Kotka, Finland. The 4986 participants received non-BLF IOLs (n = 2609) or BLF IOLs (n = 2377) in both eyes. Patients undergoing bilateral surgery between 2015 to 2016 with non-BLF IOLs (n = 102) or BLF IOLs (n = 91) and currently driving a car were interviewed using a structured questionnaire for visual performance while driving. Exposures: Follow-up for a mean (SD) of 2166 (1110) days after second eye surgery. Main Outcomes and Measures: Kaplan-Meier and multivariable Cox proportional hazards regression analyses for the risk of all-cause and traffic accident-related injuries after surgery in the second eye obtained from the patient medical records were assessed. To improve follow-up precision, both death and the end of the follow-up were used as censoring events. Results: A total of 4986 patients were included in the analysis (1707 [34.2%] men and 3279 [65.8%] women; mean [SD] age, 73.2 [8.6] years at the first surgery and 74.3 [8.8] years at the second). Injury-free survival rates preceding the first eye surgery were comparable between the non-BLF and BLF IOL groups (hazard ratio adjusted for age and sex, 0.95 [95% CI, 0.81-1.13; P =.57]). In multivariable Cox proportional hazards regression analysis controlling for age and sex, the use of BLF IOLs showed no advantage in overall injuries compared with the use of non-BLF IOLs (hazard ratio, 0.99 [95% CI, 0.88-1.11]; P =.85) or in any injury subtype. Subjective visual performance parameters for driving were all comparable between the non-BLF and BLF IOL groups except for glare when driving in the dark (evening or night), which occurred among 9 of 80 patients with BLF IOLs compared with 0 of 83 non-BLF IOLs (P <.001). Conclusions and Relevance: The findings of this cohort study suggest that use of BLF IOLs was not associated with reduced risk of injuries, whereas glare during nighttime driving was significantly worse in the BLF IOL group with pseudophakia..